factoriza cada expresión y cancela términos, por ej -(x²+2x+4)/(x+2)²=-(x+2)²/(x+2)²=-1 y (x³-27)=(x-3)(x²+3x+9) como (x³-27)/(x²+3x+9)=(x-3)(x²+3x+9)/(x²+3x+9)=(x-3)
y x³+3x²+3x+1=(x+1)³ (x+1)³/(x+1)²=(x+1) queda finalmente: (x+1)-1+(x-3)=x-1 (x+1)+(x-3)=x 2x-x-2=0 x=2
factoriza cada expresión y cancela términos, por ej
-(x²+2x+4)/(x+2)²=-(x+2)²/(x+2)²=-1
y
(x³-27)=(x-3)(x²+3x+9)
como
(x³-27)/(x²+3x+9)=(x-3)(x²+3x+9)/(x²+3x+9)=(x-3)
y x³+3x²+3x+1=(x+1)³
(x+1)³/(x+1)²=(x+1)
queda finalmente:
(x+1)-1+(x-3)=x-1
(x+1)+(x-3)=x
2x-x-2=0
x=2